Compliance with the accounting for goodwill in transitional economies: a case of Russia and Kazakhstan - Tsoy, Alexander (Auckland University of Technology, 2012)
This study aims to provide findings indicating trends in the level of compliance with the goodwill accounting by firms in Russia and Kazakhstan. Also the present paper seeks to establish whether there was a difference in the level of compliance between Russian and Kazakhstan firms. This study also intends to identify firm-specific factors that are associated with the level of compliance by firms in these countries. IFRS-compliant financial reports of 37 Russian and 17 Kazakhstan companies which disclosed the existence of goodwill were investigated. The level of compliance was measured by comparing actual disclosures made by firms with those required by IAS 36. The results indicate a generally improving trend in the level of compliance by Russian and Kazakhstan firms. However, findings suggest the existence of an unwillingness to comply with IAS 36 requirements by managers in those countries. Also the results show a higher level of compliance by Russian firms compared to that of Kazakhstan companies which may be attributed to contrasting approaches to IFRS adoption in Russia and Kazakhstan. Research findings provide evidence of a positive association of the level of compliance by Russian firms with firm goodwill intensity. The level of compliance by Kazakhstan firms appears to be positively associated with firm size. The research suggests a lack of compliance enforcement in Russia and Kazakhstan. Policy makers in Russia may consider firm goodwill intensity and policy makers in Kazakhstan firm size factors when addressing problem of non-compliance. The difference in the level of compliance between Russian and Kazakhstan firms may add to the discussion concerning pros and cons of different strategies of IFRS adoption and as such may be useful for transitional countries considering the adoption of IFRS.
Keywords: Compliance with goodwill accounting; Impairment of goodwill; IFRS adoption in transitional economies; Transparency of financial reporting